Eligibility for rt-PA within a Population: The Effect of the ECASS-3 Trial - Vinall, Phil (MD Conference Express, 2009)
According to standard emergency department (ED) guidelines, ischemic stroke patients must present to an ED within <3 hours of symptom onset to be eligible for rt-PA therapy. The European Cooperative Acute Stroke Study-3 [ECASS-3] expanded this eligibility window to 4.5 hours but with additional exclusion criteria. Even with this expanded time window, eligibility for rt-PA remains low—about 9% versus 8% for the older time window.